Dignity in the terminally ill: revisited - Chochinov, H.; Kristjanson, Linda; Hack, T.; Hassard, T.; McClement, S.; Harlos, M. (Mary Ann Liebert, Inc, 2006)
Several studies have been conducted examining the notion of dignity and how it is understood and experienced by people as they approach death.The purpose of this study was to use a quantitative approach to validate the Dignity Model, originally based on qualitative data.Themes and sub-themes from the Dignity Model were used to devise 22 items; patients were asked the extent to which they believed these specific issues were or could be related to their sense of dignity.Of 211 patients receiving palliative care, "not being treated with respect or understanding" (87.1%) and "feeling a burden to others" (87.1%) were the issues most identified as having an influence on their sense of dignity. All but 1 of the 22 items were endorsed by more than half of the patients; 16 items were endorsed by more than 70% of the patients. Demographic variables such as gender, age, education, and religious affiliation had an influence on what items patients ascribed to their sense of dignity. "Feeling life no longer had meaning or purpose" was the only vaiable to enter a logistic regression model predicting overall sense of dignity.This study provides further evidence supporting the validity of the Dignity Model. Items contained within this model provide a broad and inclusive range of issues and concerns that may influence a dying patient's sense of dignity. Sensitivity to these issues will draw care providers closer to being able to provide comprehensive, dignity conserving care.